WAYS TO IMPROVE THE PROCESS OF TEACHING A FOREIGN LANGUAGE TO UNIVERSITY STUDENTS USING ELEMENTS OF MODULAR TECHNOLOGY - Neudakhina , Yulia (Scientific practical conference, 2025)
In accordance with the Federal State Standard of Higher Education, the goal of teaching a foreign language at a university is to develop students' foreign language communicative competence. Particular emphasis on independent work of students determines the transition to technologies that contribute to more effective development of this competence. Modular organization of the process of teaching a foreign language is becoming relevant. The fundamental principles of compiling modular programs are the principles of individualization and differentiation of training.